Sentencia de casación respecto de las actuaciones de las administraciones tributarias vinculadas a actos administrativos impugnados judicialmente (Jurisprudencia) - Mejía Salazar, Álvaro Renato (2013)
Tax administrations have sometimes misunderstood the content and scope of the establish taxes power. Being a regulated activity, the establish taxes power has to observe the rules on the field, opportunity and legal powers. The court ruling object of this recession deals about the implementation of this establish taxes power in relation to the administrative acts challenged in the court. Considering that one of the purposes of the prosecution of the administrative act is their abstraction of administrative orbit of the tax authorities, it cannot apply on it any of their legal powers, including the verification. The judicial discretion on this matter makes clear that the consequences that entails for both judicial challenge administrative acts and to the tax administration.